2017
DOI: 10.1038/pcan.2016.72
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Prostate Health Index for detection of prostate cancer: results from a large academic practice

Abstract: BACKGROUNDThe Prostate Health Index (phi) outperforms PSA and other PSA derivatives for the diagnosis of prostate cancer (PCa). The impact of phi testing in the real-world clinical setting has not been previously assessed.METHODSIn a single, large, academic center, phi was tested in 345 patients presenting for diagnostic evaluation for PCa. Findings on prostate biopsy (including Grade Group [GG], defined as GG1: Gleason score [GS] 6, GG2: GS 3+4=7, GG3: GS 4+3=7, GG4: GS 8, and GG5: GS 9-10), magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 22 publications
0
51
0
2
Order By: Relevance
“…1721 It is also associated with prostate cancer aggressiveness. In 658 men with PSA levels between 4 and 10 ng/mL, phi was compared with its individual variables for the prediction of clinically significant cancer.…”
Section: Blood Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…1721 It is also associated with prostate cancer aggressiveness. In 658 men with PSA levels between 4 and 10 ng/mL, phi was compared with its individual variables for the prediction of clinically significant cancer.…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Other studies have evaluated phi in conjunction with multiparametric MRI (mpMRI), with one finding a negative predictive value of 97% for clinically significant PCa in men undergoing repeat biopsy. 21,27 This suggests that phi remains useful in an MRI-based detection paradigm.…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Tosoian et al. prospectively assessed the combination of the PHI and MRI in 345 men undergoing radical prostatectomy, and found that none of the men with a PHI <27 and PI‐RADS (prostate imaging reporting and data system) score3 had Gleason group2 PCa [30]. Further studies are needed to refine the diagnostic accuracy of PHI.…”
Section: Discussionmentioning
confidence: 99%
“…Total PSA, if quantified on other analyzers, cannot be combined with the remaining analytes, so clinical labs would need to offer this test panel in addition to any other PSA testing they've already performed. The phi test outperforms PSA alone (7) and has 90% clinical sensitivity and 31% specificity at a phi value of 27.0 (www.beckmancoulter.com), allowing for a reduction of nearly 1/3 of all biopsies while detecting 90% of cancers.…”
Section: Molecular Diagnostic Tools For Prostate Cancer: Current Non-mentioning
confidence: 99%